Teacher professional development of public elementary school: A phenomenological approach - Bahiyah, Khoridatul; Juhji, Juhji (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
A teacher must have professionalism in carrying out his duties as an educator. However, there are still many teachers who have not shown professionalism. Because it has several problems related to teacher performance, and if you have not found a solution, it can cause prolonged problems. This study aims to describe the principal's strategy for developing teacher professionalism. The research was conducted at the Gaga Ilir State Elementary School, Kronjo District, Tangerang Regency. This study uses a qualitative method with a phenomenological approach—collecting research data through observation, interviews, and documentation. Teachers and school principals serve as the primary sources of information. Data analysis went through three stages: data reduction, data presentation, and conclusions, which were carried out simultaneously with the stages. The study results indicate that teacher professionalism can develop through communication development, rewards, evaluation activities, and discussion forum activities. This finding recommends that schools can use these activities to develop teacher professionalism.